The determinants of executive pay components, incentive pay ratio and tournament's pay structure: the UK evidence - Tran, Phuong Viet (2011)
This thesis provides a review and empirical analysis of the determination of executive compensation components, long-term incentive pay ratios and the implication of tournament pay structures. The sample of 1,137 executive-year observations of comprehensive executive compensation packages from FTSE350 companies are exploited to advance our understanding of executive pay determination.